8th OpenSky Symposium 2020 2020
DOI: 10.3390/proceedings2020059003
|View full text |Cite
|
Sign up to set email alerts
|

On ADS-B Sensor Placement for Secure Wide-Area Multilateration

Abstract: As automatic dependent surveillance–broadcast (ADS-B) becomes more prevalent, the placement of on-ground sensors is vital for Air Traffic Control (ATC) to control the airspace. However, the current sensors are placed in an unstructured way that keeps some areas without coverage, and others are over-densified by sensors. Therefore, areas with coverage anomalies may cause issues that inhibit accurate ADS-B verifications as well as the availability of ADS-B altogether. In this paper, we tackle the ADS-B-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Ref. [45] proposed a solution for determining the optimal placement of ADS-B receivers on the ground. In [45], a genetic algorithm was utilized to determine the optimal placement of ADS-B receivers on the ground in the vicinity of Frankfurt Airport in Germany.…”
Section: Location Selection Problems and Surveillance Network Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [45] proposed a solution for determining the optimal placement of ADS-B receivers on the ground. In [45], a genetic algorithm was utilized to determine the optimal placement of ADS-B receivers on the ground in the vicinity of Frankfurt Airport in Germany.…”
Section: Location Selection Problems and Surveillance Network Designmentioning
confidence: 99%
“…[45] proposed a solution for determining the optimal placement of ADS-B receivers on the ground. In [45], a genetic algorithm was utilized to determine the optimal placement of ADS-B receivers on the ground in the vicinity of Frankfurt Airport in Germany. The authors first identified the required number of sensors to ensure adequate coverage of the small geographical area.…”
Section: Location Selection Problems and Surveillance Network Designmentioning
confidence: 99%
“…Notice that this marks a striking difference with respect to the known literature. Indeed, existing solutions, e.g., [29], [30], cannot change the nodes infrastructure at runtime based on robot needs nor can adequately leverage the ratio of information versus uncertainty that a new added anchor injects in the multilateration problem. Moreover, our solution is robotcentered: existing solutions usually try to optimize the entire region as a whole, with evident computational burden issues and difficulties in unknown or partially known environments, while our solution is extremely light in terms of computing power and can be computed onboard the vehicle while it explores the (possibly unknown) environments.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that this marks a striking difference with respect to the known literature. Indeed, existing solutions, e.g., [28], [29], cannot change the nodes infrastructure at runtime based on robot needs nor can adequately leverage the ratio of information versus uncertainty that a new added anchor injects in the multilateration problem. Moreover, our solution is robotcentered: existing solutions usually try to optimize the entire region as a whole, with evident computational burden issues and difficulties in unknown or partially known environments, while our solution is extremely light in terms of computing power and can be computed onboard the vehicle while it explores the (possibly unknown) environments.…”
Section: Introductionmentioning
confidence: 99%